The Person in Secular and in Orthodox-Catholic Bioethics - Bole, Thomas J. (Christian bioethics, 2000)
The following demarcates the sense of the human person in Orthodox-Catholic bioethics from the family of senses proper to secular bioethics and philosophy. The radically different sources of knowledge about the senses proper to each discipline suggest that the importation of philosophical and secular psychological distinctions and analyses into true Christianity's concern with the human person, is fundamentally misguided. This suggestion is confirmed by examination of the articles of Crosby, Glannon, Hoswepian, and Meador and Shuman.